Environmental Degradation and Climate Change: Can Globalization be the Remedy of the Problems It Has Caused? - Setyanto, Arif (Fakultas Ilmu Sosial and Ilmu Politik Universitas Jenderal Soedirman, 2025)
The accelerating pace of environmental degradation and climate change demonstrates the mounting threats in the near future. Globalization arguably plays crucial part in causing the environmental and climate problems due to the intensification of global trade and global supply chain. However, some scholars also argue that globalization serves as the avenue to promote the development of green technologies and global environmental governance which are expected to mitigate the impact of environmental problems and climate change. Against these backdrops, this paper aims to investigate whether globalization could remedy of the problems that it has caused. Using literature study, this paper examines current global development of green technologies and global environmental governance as global efforts in mitigating the impact of environmental and climate problems. By focusing on the development of solar panel and electric vehicle (EV) as green technologies as well as the UNFCCC and Paris Agreement as the global environmental governance, the findings suggest that current globalization still could not effectively address and mitigate the environmental and climate problems that it has caused. Keywords: globalization, environmental degradation, climate change, green technologies, global environmental governance.